2007
DOI: 10.17221/738-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Determination of polydextrose as a fat replacer in butter

Abstract: Míčková K., Čopíková J., Synytsya A. (2007): Determination of polydextrose as a fat replacer in butter. Czech J. Food Sci., 25: 25-31.Polydextrose is used in several countries as a low caloric sugar and fat substitute (bulking agent). It is prepared by condensation of glucose, d-glucitol, and citric acid (89:10:1). The resulting condensation product has no chemically defined structure but it represents a mixture of polymerisation products. The determination of polydextrose in butter is complicated owing to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, Sudha et al (2007) reported fat replacement in biscuits by incorporation of polydextrose, maltodextrins, and simplesse. Polydextrose is glucooligosacchrieds that is resistant to digestion and is also known to replace butter in many dairy foods, especially in bakery products (Mickova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sudha et al (2007) reported fat replacement in biscuits by incorporation of polydextrose, maltodextrins, and simplesse. Polydextrose is glucooligosacchrieds that is resistant to digestion and is also known to replace butter in many dairy foods, especially in bakery products (Mickova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect of excessive dietary fat consumption is virtually universal, and numerous chronic diseases are linked to high fat intake, among them coronary heart diseases (CHD) are listed on top. Several studies have indicated that the high postprandial serum triglyceride (TAG) concentration is a leading risk factor and is related to high fat intake, particularly saturated fat (Mickova et al, 2007). The serum TAG peak is raised during 2-6 hours of meal intake and indicates the long frequency in eating habits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sudha et al (2007) reported fat replacement in biscuits by incorporation of polydextrose, maltodextrins, and simplesse. Polydextrose is gluco-oligosacchrieds that is resistant to digestion and is also known to replace butter in many dairy foods, especially in bakery products (Mickova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides as biological macromolecules exhibit a variety of distinct physicochemical, physiological, and pharmaceutical properties (Jiang et al, 2013;Li et al, 2014;MíčKoVá,čopíKoVá, & SyNytSyA, 2007). Most polysaccharides are obtained from plants, animals, and microorganisms (Qu, Liu, & Zhang, 2014;Vu, Chen, Crawford, & Ivanova, 2009;Zia, Anjum, Zuber, Mujahid, & Jamil, 2014).…”
Section: Introductionmentioning
confidence: 99%